Longitudinal assessment of natural disease progression in Brazilian children and adolescents with Charcot-Marie-Tooth disease - Soares, Bruno Alvarenga; Freitas, Camila Fernanda de; Cardoso, Juliana; Baptista, Cyntia Rogean de Jesus Alves de; Marques, Wilson, Junior; Mattiello-Sverzut, Ana Claudia (Arquivos de Neuro-Psiquiatria, 2025)
Charcot-Marie-Tooth disease (CMT) is a progressive neurological disorder that typically manifests in early childhood. The natural progression of CMT in Brazilian pediatric and adolescent populations remains unknown.To evaluate the natural disease progression in Brazilian children and adolescents with CMT using the Charcot-Marie-Tooth Pediatric Scale (CMTPedS).A longitudinal observational study was conducted to assess disease progression over a 2-year period through 3 evaluations, spaced 1 year apart, in children and adolescents aged 5 to 18 years with a confirmed CMT diagnosis. Height, weight, body mass index (BMI), fat-free mass, and functionality (assessed via the CMTPedS) were evaluated in each of the three sessions.We included 30 participants of both sexes with a mean age of 11.1 ± 3.2 years. Significant increases in height, weight, and BMI were observed, alongside a decline in the percentage of lean body mass across evaluations. The total score on the CMTPedS increased by 4.5 points throughout 2 years, indicating disease progression, with notable deterioration in functional dexterity, pinprick and vibration sensations, and gait. Significant progression was evident within 1 year, with an average annual deterioration of 2.25 points. The subgroup with CMT type 1A (CMT1A) presented an increase of 4 points in the total score, corresponding to an average annual progression of 2 points. Unlike the overall CMT group, the CMT1 subgroup did not exhibit a decline in the pinprick sensation score.Children and adolescents with CMT exhibit significant disease progression within 2 years, with measurable deterioration observed as early as 1 year. The CMTPedS is a reliable tool to monitor CMT progression in this population.
Keywords: Charcot-Marie-Tooth Disease; Functional Status; Disability Evaluation; Child; Adolescent